Pengolahan Data Keuangan Menggunakan Zahir Accounting 5.1 Pada Toko Ujang Ekon Depok - Ahmad Al Kaafi; Nurul Fahmi Lestari (Akasia: Artikel Ilmiah Sistem Informasi Akuntansi, 2022)
These rapid developments have had a major impact on the world of trade. Examples of technology that is widely used in the commercial world is computer technology. Especially in the retail sector, helping to ensure the company's activities are carried out effectively and efficiently. Ujang Ekon Depok electrical shop requires a computerized accounting information system. Processing of accounting data is still done manually such as errors in recording, loss of transaction documents that occur every day so that the presentation of financial reports is not accurate and is still considered not in accordance with existing accounting data processing standards. To solve the problems faced, this company requires a special accounting application that is easy to understand and easy to implement. Zahir Accounting Version 5.1 is the right solution to solve the problems that exist in this company that is easy to understand and easy to implement, so that accounting data processing at the Ujang Ekon Depok electricity shop can run more effectively and efficiently compared to using manual processing